Analysis of problems and risks of the market system services of power industry of Kazakhstan (Journal of Economic Research & Business Administration, 2015)
The risks connected with system services, have to cope with the help of various tools. According to the estimates of experts, for ensuring uninterrupted functioning of a power system many countries use more than twenty different system services.Research of the market of Kazakhstan shows that only system services can provide a high quality of power supply and shortly it becomes independent views of the electrical power sphere.
Keywords: system services; network reservation; risks of power supply; liberal market of the electric power